2008
DOI: 10.1103/physrevlett.100.195302
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Superfluid-Turbulence Cascade by its Low-Temperature Cutoff

Abstract: On the basis of a recently proposed scenario of the transformation of the Kolmogorov cascade into the Kelvin-wave cascade, we develop a theory of low-temperature cutoff. The theory predicts a specific behavior of the quantized vortex line density, L, controlled by the frictional coefficient, alpha(T)<<1, responsible for the cutoff. The curve ln L(lnalpha) is found to directly reflect the structure of the cascade, revealing four qualitatively distinct wave number regions. Excellent agreement with a recent exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…On the other hand, at length scales smaller than the mean vortex spacing the energy is transferred along each vortex through a Kelvin-wave cascade; this regime has no classical analog and can be called quantum. Several theoretical considerations of the classical-quantum crossover have been proposed [58,59,60], but this topic is not yet settled and remains controversial.…”
Section: T) (10)mentioning
confidence: 99%
“…On the other hand, at length scales smaller than the mean vortex spacing the energy is transferred along each vortex through a Kelvin-wave cascade; this regime has no classical analog and can be called quantum. Several theoretical considerations of the classical-quantum crossover have been proposed [58,59,60], but this topic is not yet settled and remains controversial.…”
Section: T) (10)mentioning
confidence: 99%
“…Here the anomaly in the temperature dependence of the effective turbulent viscosity ν′ was observed, in a way similar to the shoulder in the front velocity V f in our experiments. The current explanation of this effect is linked to the physics of the crossover region in the turbulent energy cascades (46). We note, however, that the decrease of ν′ is observed in the temperature region where Re α ∼ Re λ ∼ 10 3 , and thus the influence of the decoupling cannot be a priori excluded.…”
Section: Discussionmentioning
confidence: 86%
“…Within the former (coarse-grained flow on length scales greater than the mean separation between vortex lines), the regions of enhanced vorticity, i.e., those with an enhanced density of vortex lines, will be most visible. Within the latter (small length scales that resolve discrete vortex lines), one will be able to observe such processes as vortex reconnections, Kelvin waves, and the emission and absorption of small vortex loops-which are believed to be responsible for the quantum cascade of energy and control the dissipation of the vortex tangle [3,4].Micron-sized particles of solid hydrogen have already been used to tag vortex cores at high temperatures, T $ 2 K [5,6]; however, the invasive means of introduction and relatively large particle size preclude implementation of this technique for low temperatures and small length scales. Potentially ideal tracers would be metastable molecules He à 2 in the spin triplet state, which have a relatively long lifetime of ð13 AE 2Þ s [7].…”
mentioning
confidence: 99%
“…Each molecule can be visualized many times by laser fluorescence [10], and single-molecule resolution is, in principle, possible. It was shown that the excimers can serve as tracers of the normal component in superfluid 4 He at temperatures above 1 K [11], and visualization has been successfully demonstrated [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation